Implementasi Manajemen Pembelajaran Saintifik di Institut Agama Hindu Negeri Tampung Penyang Palangka Raya - I Putu Widianto (Satya Widya: Jurnal Studi Agama, 2019)
This study is to describe the implementation of learning management in subjects that use scientific learning at the IAHN-TP Palangka Raya. This research approach uses a qualitative approach using descriptive design. The research was conducted in Institut Agama Hindu Negeri Tampung Penyang Palangka Raya Indonesia. The researcher collected various information by structured interviews and disguised observations. Analysis of interview data with an interactive model analysis model from Miles and Huberman and analysis of data from observations carried out by the checklist method. The results showed the stages of scientific learning management consisted of stages of learning planning, implementation of learning and supervision of learning.